A lift‐net method for capturing diving and sea ducks. (23rd August 2013) - Ware, Lindsay L.; Naumann, Benjamin T.; Wilson, Philip L.; Petrie, Scott A.; Schummer, Michael L.
ABSTRACT Alternatives to bait‐trapping waterfowl are often necessary when studying health or body condition, when targeting species that are not easily attracted to bait or those that occur in deep‐water habitats where bait‐trapping can be difficult. We designed an active netting method for capturing diving and sea ducks, which we deployed at 8 sites in Lake Ontario, Canada from 2006 to 2007 and 2011 to 2012. A mist net suspended horizontally 0.5 m below the water surface was lifted out of the water when ducks swam over the capture area. The technique requires a stationary structure to anchor one end and is lifted out of the water by hand or using a vehicle on the non‐anchored end using attached ropes. We used structures including docks and walls of a shipping channel to secure ropes, but other structures could be used. Catch rates were 0.63 birds/hr for greater scaup (Aythya marila), and 0.65 birds/hr for long‐tailed ducks (Clangula hyemalis). In comparison, catch rates for floating mist nets were 0.08 birds/hr and 0.86 birds/hr for greater scaup and long‐tailed ducks, respectively. Equipment costs to build a lift‐net were 85% less than to build a floating mist net. © 2013 The Wildlife Society.